Analisis Faktor Safety Climate untuk Meningkatkan Keselamatan dan Kesehatan Kerja pada Pekerjaan Konstruksi di PT XYZ Bunyu Field - Haki, Zulfani; Achmadi, Fuad; Vitasari, Prima (Universitas Katolik Parahyangan, 2025)
The industry of oil and gas is a something complex, there are many potential hazards and risks that cause quite high work accidents, for example, the dangers of toxic gases, explosion hazards, fire hazards, electrical hazards, moving equipment hazards, and gravity hazards caused by lifting operations. Based on the observations in the field, many jobs were found to be stopped because to finding related to unsafe actions and unsafe conditions in the location that could be exposed to equipment and workers, so that they could cause material losses and fatalities. Action that can be taken to improve the occupational health and safety are by making a good safety climate in the work location. The research is to improve the occupational health and safety provide the improvement solutions based on safety climate factors that the most role in improving occupational health and safety in construction work activity. Explpratory Factor Analysis used to describe data structure and interconnected structure analyze in a number of variables by making a factor. The factor analysis results show a total variance of 86.538%. The most dominant factor in the safety climate regarding occupational health and safety in construction work is the training and compliance factor, while the factor that is not dominant is the occupational health and safety promotion factor which is based on the magnitude of the eigenvalue.